Sensorimotor Rhythm-Brain Computer Interface With Audio-Cue, Motor Observation and Multisensory Feedback for Upper-Limb Stroke Rehabilitation: A Controlled Study - Li, Xin; Wang, Lu; Miao, Si; Yue, Zan; Tang, Zhiming; Su, Liujie; Zheng, Yadan; Wu, Xiangzhen; Wang, Shan; Wang, Jing; Dou, Zulin (Frontiers in Neuroscience, 2022)
Several studies have proved positive clinical effect of brain computer interface (BCI) training for stroke rehabilitation. This study investigated the efficacy of the sensorimotor rhythm (SMR)-based BCI with audio-cue, motor observation and multisensory feedback for subacute stroke rehabilitation. Furthermore, we discussed the impact of intensive BCI training, which has not been mentioned in other studies. 24 subacute stroke patients with severe upper limb (UL) motor deficits were randomly assigned to 2 groups: 2-week SMR-BCI training combined with conventional treatment (BCI Group, BG, n=12) and 2-week conventional treatment without SMR-BCI intervention (Control Group, CG, n=12). Motor function was measured using clinical measurement scales, including Fugl-Meyer Assessment-Upper Extremities (FMA-UE; primary outcome measure), Wolf Motor Functional Test (WMFT), and Modified Barthel Index (MBI), at baseline (Week 0), post-intervention (Week 2), and follow-up week (Week 4). EEG data from patients allocated to the BG was recorded during intervention sessions and quantified by mu suppression. All functional assessment scores (FMA-UE, WMFT, and MBI) significantly improved at Week 2 for both groups (p < 0.05). The BG had significantly higher motor functional improvement at Week 4 compared to the CG. The mu suppression of bilateral hemisphere both had a positive trend with the motor function at Week 2. This study proposes a new effective SMR-BCI system and demonstrates that the SMR-BCI training with audio-cue, motor observation and multisensory feedback, together with conventional therapy can promote long-lasting UL motor improvement. In addition, a new training prescription (higher intensive SMR-BCI) would have a positive effect on subacute stroke recovery.